THE INFLUENCE OF LIFESTYLE, SELF-CONTROL, AND PARENTAL INCOME ON FINANCIAL BEHAVIOR OF STUDENTS IN THE AL-QURAN AL-AMIN ISLAMIC BOARDING SCHOOL PABUWARAN, PURWOKERTO - Soli Solihat; Aula Ahmad Hafidh Saiful Fikri (International Journal of Teaching and Learning, 2024)
This research aims to analyze the influence of lifestyle, self-control, and parental income on the financial behavior of students at Pondok Pesantren Al-Quran Al-Amin Pabuwaran Purwokerto. This study is a quantitative descriptive research. The subjects in this study are students residing at Pondok Pesantren Al-Quran Al-Amin Pabuwaran. The population in this study consists of 544 students. The sample size in this study is 85 students. The sampling technique used is simple random sampling. The data analysis technique used is Structural Equation Modeling (SEM) with the assistance of SmartPLS version 3.0 for Windows. The research findings indicate: 1) There is a significant influence of lifestyle on the financial behavior of students at Pondok Pesantren Al-Quran Al-Amin Pabuwaran Purwokerto with a path coefficient value of 0.344, a T-statistic value of 3.900 > 1.96, and a P-value of 0.000 < α (0.05). 2) There is a significant influence of self-control on the financial behavior of students at Pondok Pesantren Al-Quran Al-Amin Pabuwaran Purwokerto with a path coefficient value of 0.358, a T-statistic value of 3.957 > 1.96, and a P-value of 0.000 < α (0.05). 3) There is no significant influence of parental income on the financial behavior of students at Pondok Pesantren Al-Quran Al-Amin Pabuwaran Purwokerto with a path coefficient value of -0.181, a T-statistic value of 1.118 < 1.96, and a P-value of 1.534 > α (0.05).